TINJAUAN ISLAM TERHADAP KETIDAKEFEKTIFAN POLITIK BARAT DALAM MENOPANG TATANAN SOSIAL MASYARAKAT - SAIPUL NASUTION; YAUMI SA’ADAH; TEGUH EKA PRASETYA; MUHAMMAD AZRUL AMIRULLAH (UIN Mataram, 2026)
Western political concepts rooted in secularism, liberalism and rationalism have become the dominant currents in organizing the lives of modern societies. However, in practice, this model often fails to ensure social justice, societal stability, and the integration of moral values in the power structure. This article aims to analyze the fundamental weaknesses in the Western political system, especially in terms of ensuring a harmonious and just social order. Through a normative and descriptive approach, this study uses the perspective of Islamic law as a tool of criticism, which emphasizes the importance of the values of tawhid, justice (al-adalah), benefit (maṣlaḥah), and the responsibility of power (al-mas'ūliyyah). The analysis shows that Islamic politics offers a more complete ethical and transcendental framework in sustaining social life, compared to Western politics that tend to be technocratic and pragmatic. Thus, it is necessary to reorient global political thought so that it does not only focus on legal-formal aspects, but also on the spiritual and moral dimensions that are at the core of Islamic law.